The Effect of Corporate Governance Mechanism, Company’s Growth and Company Performance toward Going Concern Audit Opinion in Non-Financial Service Companies for the Period of 2012-2015 - Setyarini Santosa, S.E., MAFIS, Ak.; Dian Riesta Untari (President University Press, 2017)
A company receiving going concern audit opinion from public audit firm can be a sign that the company is in doubt to have a long business run, according to the auditor judgment. The aim of this study is to investigate the determinant of company’s likelihood to receive a going concern opinion from auditor in the Indonesian capital market context. In order to discover the factors behind a company receiving going concern audit opinion, this study employs a logistic regression method, with the dependent variables of going concern audit opinion and the independent variables of corporate governance mechanism, company’s growth, and company’s performance. In detail, researcher choses board size, independent commissioner, institutional ownership, management ownership to define corporate governance. As for company’s performance, researcher employs liquidity, profitability and solvency ratios. Researcher uses data from non-financial service companies listed in Indonesian stock exchange during the period of 2012-2015. The result shows a significant effect of institutional ownership, board size, liquidity and solvency toward the going concern audit opinion.